Refugee Impacts on Turkana Hosts : A Social Impact Analysis for Kakuma Town and Refugee Camp, Turkana County, Kenya - Vemuru, Varalakshmi; Oka, Rahul; Gengo, Rieti; Gettler, Lee (World Bank, Washington, DC, 2017)
In June 2015, the World Bank in partnership with United Nations High Commissioner for Refugees (UNHCR) and the University of Notre Dame, conducted an economic and social impact analysis of refugees on hosts in Turkana County, Northwestern Kenya, occupied by the Turkana community (pop. 1.2 million) and Kakuma Refugee Camp (pop. 200,000). Renowned for their herding abilities in the harsh arid landscape of Turkana County, the Turkana host community has been systematically marginalized from mainstream development programs under both colonial and post-colonial governments, and are among the most impoverished groups in Sub‐Saharan Africa. The goal was to measure the economic and social impact of the refugees on the Turkana community. The study finds that while the Turkana overall continue to show extremely low indicators of socio‐economic and physical‐emotional well‐being, there is a net positive impact on the local Turkana communities of Kakuma who engage with the refugees in Kakuma. These impacts are seen in greater access to: (1) cash, credit, and consumption through exchange of goods, labor, and services; (2) health and educational facilities established for the refugees; and (3) nutritional security measured through biological indicators such as sum of skinfolds and body mass index. The results also suggest that the Turkana host community at Kakuma has developed a complex counter‐narrative of refugees as good and beneficial in opposition and mitigation to the meta‐narrative of refugee as violent economic burdens.